Effect of the Dental Office Environment and the Dentist's Attire on children's cooperation - Ijaz, Faiza; Umar, Ahmed; Ayub, Uzair; Fayyaz, Zahra; Bajwa, Sikandarjaved; Rashid, Asma; Babar, Bilal Zaman; Khurshid, Maryam; Abbas, Tanveer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this cross-sectional descriptive study was to ascertain children's dental clinic choices in order to alleviate anxiety during dental operations. This study employed a survey approach. Methods: A questionnaire was developed to identify a child's choice for a dental facility in order to ease anxiety associated with dental procedures. The research enrolled 92 children aged 7–10 years. The kids were arbitrarily chosen following their initial dental appointment at a private dental institution. Data were analysed using SPSS. The Chi-squared test was used to compare responses to questionnaire questions across age and gender categories. P 0.05 was deemed significant statistically. Results: The demographic data of 92 kids shows that 34% Boys prefer male dentists, whereas 28% girls prefer female dentists. Majority of females opting for lab coats at 23%. Also, 11% of boys and 11% of girls preferred a dentist in surgical gowns. 86% of the kids who were asked like having cartoons on their doctor's office walls. Among them, 50 (54.3%) of the boys liked clinics with cartoon paintings the best. Conclusion: The outcomes of this study will help the dental team build a comfortable dental environment for children, lowering anxiety and enhancing overall treatment quality.